Trajectories of quality of life recovery and symptom burden after autologous hematopoietic cell transplantation in multiple myeloma. Issue 1 (21st May 2022) - D'Souza, Anita; Brazauskas, Ruta; Stadtmauer, Edward A.; Pasquini, Marcelo C.; Hari, Parameswaran; Bashey, Asad; Callander, Natalie; Devine, Steven; Efebera, Yvonne; Ganguly, Siddhartha; Gasparetto, Cristina; Geller, Nancy; et al.
Abstract: Early autologous hematopoietic cell transplantation (AHCT) with post‐transplant maintenance therapy is standard of care in multiple myeloma (MM). While short‐term quality of life (QOL) deterioration after AHCT is known, the long‐term trajectories and symptom burden after transplantation are largely unknown. Toward this goal, a secondary analysis of QOL data of the BMT CTN 0702, a randomized controlled trial comparing outcomes of three treatment interventions after a single AHCT ( N = 758), was conducted. FACT‐BMT scores up to 4 years post‐AHCT were analyzed. Symptom burden was studied using responses to 17 individual symptoms dichotomized as 'none/mild' for scores 0–2 and 'moderate/severe' for scores of 3 or 4. Patients with no moderate/severe symptom ratings were considered to have low symptom burden at 1‐year. Mean age at enrollment was 55.5 years with 17% African Americans. Median follow‐up was 6 years (range, 0.4–8.5 years). FACT‐BMT scores improved between enrollment and 1‐year and remained stable thereafter. Low symptom burden was reported by 27% of patients at baseline, 38% at 1‐year, and 32% at 4 years post‐AHCT. Predictors of low symptom burden at 1‐year included low symptom burden at baseline: OR 2.7 (1.8–4.1), p < 0.0001; older age: OR 2.1 (1.3–3.2), p = 0.0007; and was related to being employed: OR 2.1 (1.4–3.2), p = 0.0004). We conclude that MM survivors who achieve disease control after AHCT have excellent recovery of FACT‐BMT and subscale scores to population norms by 1‐year post‐transplant, though many patients continue to report moderate to severe severity in some symptoms at 1‐year and beyond. Abstract : Change in FACT‐BMT score between baseline and 1‐year post‐transplant after AHCT. Q4 represents the highest QOL score quartile and Q1 represents the lowest QOL score quartile.